Ekonomiczne warunki reaktywowania samorządu terytorialnego w Polsce - Wierzbicki, Janusz (Wydział Prawa i Administracji UAM, 1991)
Polish territorial self-government has been reactivated 40 years after its abolishment in 1950. During the past period, the powers of self-government were taken over by lrcal organs of central state administration. Subsequently, the latter organs were subject to decentralization. However, due to political reasons this process could not have achieved its objectives. The change of the political system in 1990 could bring self-government back to life. Nevertheless, its formation meets many obstacles. A strong need is felt to work out a new model of self-government, adequate to a considerable increase in social and economic functions of a modern state. The scope of the self-government activity is nowadays much larger than in the past and thus it is no longer possible to reactivate the traditional system of self-government whose activity could be financed from its own revenues. Besides, it is equally difficult to make a self-government system in the Polish socio-economic conditions similar to the one operating in modern West Europen countries, with its wide scope of activity and powers. A particular difficulty arises from the fact that the Polish self-government model must take into account a critical state of economy and budget during the process of implementing the economic reforms. In effect, the Polish self-government system of today retains some elements of mechanisms functioning during the decentralization of central state administration, especially the mechanism of adjusting subsidies for local organs~to the scope of their tasks. Difficulties in balancing the central budget make it impossible for self-government to carry out its functions. Moreover, it turns out that it is far from easy to subsidize the self-government activity without limiting its independence. In such conditions there exists the danger of weakening the position of self- -government and obliterating the differences between self-government and central state administration. The democratic procedure of electing the self-government organs cannot alone be considered sufficient for the realization of aspirations of the local population to decide independently about the satisfaction of its own needs.
Economic and financial conditions of reactivating territorial self-government in Poland